Bridge Average Value Model of Modular Multilevel Converter - Ning CHEN; Lei QI; Meng BAO; Xiang CUI (Zhongguo dianli)
The speed-up simulation model of modular multilevel converter (MMC) is the basis for the research of voltage-source converter high-voltage direct-current (VSC-HVDC) system. Among many models, the bridge Thevenin model of MMC is the most widely used. In this paper, it is found that the simulation speed can be further improved. Based on the Thevenin equivalent circuit of MMC’s bridge, a new bridge average value model (AVM) is proposed by using the idea of energy equalization. The proposed model significantly reduces the computational burden of Thevenin model and improves the simulation efficiency of the model. The simulation results show that the model can be applied to the application scenarios of circulating current suppression, AC/DC side fault simulation and so on, in which cases that do not pay attention to the capacitor voltage of sub-modules.